2017
DOI: 10.1021/acsmacrolett.7b00310
|View full text |Cite
|
Sign up to set email alerts
|

Unique Base-Initiated Depolymerization of Limonene-Derived Polycarbonates

Abstract: The depolymerization of poly(limonene carbonate) (PLC) initiated by 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) was investigated. The strong organic base TBD was capable of deprotonating the OH-terminated PLC, leading to fast degradation via backbiting reactions at high temperature. An interesting feature of the base-initiated breakdown of PLC lies in the quantitative depolymerization into the corresponding initial limonene oxide monomer. This result implies the complete back-to-monomer recyclability of the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 39 publications
1
79
3
1
Order By: Relevance
“…These biobased polymers hold great potential for practical utilization, given both their excellent sustainability profile (with complete back-to-monomer recyclability) 19 and a vast scope of potential applications, which include protecting coatings, 20 breathing-glass windows, 10 and the addition of permanent antibacterial activity and hydrophilization. 11…”
Section: Limonene Carbonatesmentioning
confidence: 99%
“…These biobased polymers hold great potential for practical utilization, given both their excellent sustainability profile (with complete back-to-monomer recyclability) 19 and a vast scope of potential applications, which include protecting coatings, 20 breathing-glass windows, 10 and the addition of permanent antibacterial activity and hydrophilization. 11…”
Section: Limonene Carbonatesmentioning
confidence: 99%
“…With the same objective of building a sustainable polymer cycle, another recent example involved the depolymerisation of an innovative limonene-based polycarbonate into a limonenederivative epoxide, using TBD as catalyst. 84 In this study, Li et al demonstrated that the scission of the polymer chain was initiated by the deprotonation of the hydroxyl chain ends of the polymer before a chain transfer process released one molecule of monomer (Scheme 12b). This mechanism selec-Scheme 10 Depolymerisation of PHB into TBL.…”
Section: Emerging Opportunitiesmentioning
confidence: 95%
“…8) through a back-biting mechanism. 117 Such controlled depolymerisation can set the basis for efficient recycling of PLC and developing sustainable material solutions based on a renewable building block. 118…”
Section: Minireviewmentioning
confidence: 99%